SOCIAL MEDIA SHOULD BECOMING TOOL FOR ESTABLISH UNIVERSAL COMPASSION FOR ALL PEOPLE AS ONE SOLUTION TO SOLVE THE PANDEMIC COVID-19 PROBLEM - Prasanthy Devi Maheswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The Vedas state that humankind is the perfect creature. Humankind is the representation of God on the earth. However, because of the Kali-yuga character's effect, humankind and all things experienced degradation and even chaos. Sloka of Manusmṛti I.85 stated: